Enhanced Hydrogen Production from Biomass Pyrolysis using Surfactant-Modified Na-Bentonite Catalyst - Irawan, Dwi; Wijayanti, Widya; Wahyudi, Slamet; Kusumo, Herma Nugroho Rono Adi; Yani, Ahmad; Wardana, I.N.G. (ASEAN Journal of Science and Engineering, 2025)
This study investigates the improvement of hydrogen gas production in biomass pyrolysis through the use of Na-bentonite catalysts modified with methyl ester sulfonate (MES), a biodegradable anionic surfactant. Corn cob powder was used as the biomass feedstock in a fixed-bed pyrolysis reactor at 550°C. The MES modification introduced alkyl, ester, and sulfonate functional groups, increasing the catalyst porosity, surface area, and acidity. Structural and chemical changes were confirmed by FTIR, XRD, UV-Vis, SEM, and EDX analyses. The MES-modified Na-bentonite catalyst significantly enhanced hydrogen production, reaching 876 ppm (a 25.11% increase compared to pyrolysis without a catalyst) and also lowered the reaction temperature and shortened the reaction time. Methane production decreased as MES improved catalyst selectivity toward dehydrogenation pathways. The results indicate that MES-modified Na-bentonite is a low-cost, efficient, and environmentally friendly catalyst suitable for improving hydrogen yields in biomass pyrolysis, offering a promising alternative to conventional metal-based catalysts.